(untitled) (Research, Society and Development, 2021)
Herpes zoster (HZ) – a viral infection commonly known as shingles – is caused by reactivation of the varicella-zoster virus (VZV), one of eight known herpes viruses that infect humans. It is ubiquitous and highly contagious, with initial exposure usually occurring during childhood, when it causes chickenpox. The mechanism responsible for reactivating the virus is still not fully understood. However, it appears to be associated with a weakened immune system, with stress also having been identified as a possible triggering factor. Vesicular-bullous lesions on the skin that follow the pathway of a particular nerve are typically the clinical basis for diagnosing HZ with no need for further laboratory testing. The objective of this study is to report a clinical case of a patient, 17 years old, diagnosed with HZ in the trigeminal nerve with involvement of the mandibular branch. There were vesicular-bullous skin lesions in the mesenteric region, the mandibular region and the lower lip, in addition to erythematous lesions on the tongue, with pain in all the affected regions. All lesions were located on the left side of the face and did not exceed the midline. The treatment was performed with acyclovir and pain medication (Paracetamol and Codeine Phosphate, Tylex® 30mg), with complete resolution occurring in 30 days. The patient is undergoing a 6 month outpatient follow-up and did not exhibit any functional sequelae.